m6A methylation-induced NR1D1 ablation disrupts the HSC circadian clock and promotes hepatic fibrosis - Li Chen; Siwei Xia; Feixia Wang; Yuanyuan Zhou; Shuqi Wang; Ting Yang; Yang Li; Min Xu; Ya Zhou; Desong Kong; Zili Zhang; Jiangjuan Shao; et al. (Elsevier, 2023)
The roles of nuclear receptor subfamily 1 group d member 1 (NR1D1) and the circadian clock in liver fibrosis remain unclear. Here, we showed that liver clock genes, especially NR1D1, were dysregulated in mice with carbon tetrachloride (CCl4)-induced liver fibrosis. In turn, disruption of the circadian clock exacerbated experimental liver fibrosis. NR1D1-deficient mice were more sensitive to CCl4-induced liver fibrosis, supporting a critical role of NR1D1 in liver fibrosis development. Validation at the tissue and cellular levels showed that NR1D1 was primarily degraded by N6-methyladenosine (m6A) methylation in a CCl4-induced liver fibrosis model, and this result was also validated in rhythm-disordered mouse models. In addition, the degradation of NR1D1 further inhibited the phosphorylation of dynein-related protein 1-serine site 616 (DRP1S616), resulting in weakened mitochondrial fission function and increased mitochondrial DNA (mtDNA) release in hepatic stellate cell (HSC), which in turn activated the cGMP-AMP synthase (cGAS) pathway. Activation of the cGAS pathway induced a local inflammatory microenvironment that further stimulated liver fibrosis progression. Interestingly, in the NR1D1 overexpression model, we observed that DRP1S616 phosphorylation was restored, and cGAS pathway was also inhibited in HSCs, resulting in improved liver fibrosis. Taken together, our results suggest that targeting NR1D1 may be an effective approach to liver fibrosis prevention and management.